2017
DOI: 10.1016/j.ajme.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of formalin-treated cadaver on medical students, staff members, and workers in the Alexandria Faculty of Medicine

Abstract: Background: Formaldehyde can be toxic, allergenic and carcinogenic. Evaporation of formaldehyde from formalin-treated cadavers in the anatomy dissection rooms can produce high exposure. This study was conducted to assess acute and chronic toxic effects of formalin-treated cadavers on medical students, staff members, and workers at the Anatomy department in the Alexandria Faculty of Medicine (AFM). Methods: A cross sectional approach was adopted to investigate medical students (n = 454). Staff members and worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…Some individuals were highly sensitive to the FA while others were more resistant and had no reaction to the same level of exposure [ 40 ]. In our study, the most frequent complaint reported by the exposed students was the unpleasant smell (78.8%) ( Figure 9 ), and this occurrence is consistent with some previous studies which also reported this symptom as the most predominant one at 68% [ 21 ], 80% [ 41 ], 77% [ 42 ], 57.5% [ 35 ], 91.2% [ 43 ] and, 70.3% [ 44 ]. This common finding simply reflects that FA exposure is mainly by inhalation during the dissection sessions.…”
Section: Resultssupporting
confidence: 91%
“…Some individuals were highly sensitive to the FA while others were more resistant and had no reaction to the same level of exposure [ 40 ]. In our study, the most frequent complaint reported by the exposed students was the unpleasant smell (78.8%) ( Figure 9 ), and this occurrence is consistent with some previous studies which also reported this symptom as the most predominant one at 68% [ 21 ], 80% [ 41 ], 77% [ 42 ], 57.5% [ 35 ], 91.2% [ 43 ] and, 70.3% [ 44 ]. This common finding simply reflects that FA exposure is mainly by inhalation during the dissection sessions.…”
Section: Resultssupporting
confidence: 91%
“…Formate can cause crosslinking of nucleic acids and amino acids causing cell death which is the main factor making formalin carcinogenic. The other symptoms seen are running nose (39%) which was about 69.5% in a study done by Elshaer et al 6 Headache (38%), lack of concentration (25%) and sore throat (20%) are the other main symptoms in our study. In a study done by Koirala et al Nausea was found to be about 69.8% contrary to our study which was 23%.…”
Section: Discussionsupporting
confidence: 56%
“…Nurses and clinicians have different occupational and ergonomic problems (Afshari et al, 2014). However, formaldehyde poses a health risk for nurses, clinicians and physicians (Elshaer and Mahmoud, 2017) but even more so for those employed in the healthcare industry as these individuals may be exposed to formaldehyde, in addition to other various genotoxic substances. So, the risk assessment of occupational exposure to chemicals is an important step in chemical monitoring and control in pathology departments.…”
Section: Introductionmentioning
confidence: 99%